2011
DOI: 10.1089/vbz.2010.0065
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey Study of Toscana Virus in Domestic Animals, Granada, Spain

Abstract: Toscana virus (TOSV) is transmitted by infected sandflies. In Mediterranean countries, TOSV is one of the major viral pathogens involved in aseptic meningitis and meningoencephalitis in humans. It remains unclear if there are animal reservoirs able to maintain the virus through the cold months of the year, when the vector is not circulating. From May to October of 2006 and 2007, we conducted a serosurvey study on domestic animals from Granada province (southern Spain). TOSV was investigated in 1186 serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…12 In a recent serosurvey undertaken in Granada, Spain, another TOSV-endemic region where the virus could be detected in sandflies and clinical cases, a high seroprevalence rate for TOSV antibodies (36.2%) among 1,186 domestic animals was revealed. 13 Here, IgG detection rates of 64.3% in horses, 59.6% in cats, 48.3% in dogs, 32.3% in sheep, 22% in pigs, 17.9% in cows, and 17.7% in goats were reported. Though cross-reactions among phleboviruses within the sandfly fever Naples virus serocomplex cannot be excluded and might have resulted in an overestimation of the seroprevalence in this study, the overall data are compatible with a TOSV-endemic zone and in agreement with the feeding habits of P. perniciosus, the documented vector in the region.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…12 In a recent serosurvey undertaken in Granada, Spain, another TOSV-endemic region where the virus could be detected in sandflies and clinical cases, a high seroprevalence rate for TOSV antibodies (36.2%) among 1,186 domestic animals was revealed. 13 Here, IgG detection rates of 64.3% in horses, 59.6% in cats, 48.3% in dogs, 32.3% in sheep, 22% in pigs, 17.9% in cows, and 17.7% in goats were reported. Though cross-reactions among phleboviruses within the sandfly fever Naples virus serocomplex cannot be excluded and might have resulted in an overestimation of the seroprevalence in this study, the overall data are compatible with a TOSV-endemic zone and in agreement with the feeding habits of P. perniciosus, the documented vector in the region.…”
Section: Discussionmentioning
confidence: 66%
“…32 Interestingly, attempts of virus isolation were unsuccessful in all samples and a low level of TOSV viremia was detected only in one goat, suggesting an ongoing virus circulation in the region with evidence of previous exposure and low incidence of recent infections. 13 In Tunisia, another Phlebovirus-endemic region, TOSV as well as Punique and Sandfly fever Sicilian virus exposure in dogs were identified, with 7.5% seroprevalence for TOSV. 33 It has further been suggested that dogs can be used as sentinel animals for monitoring Phlebovirus activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have revealed a probable epidemiologic interaction among these agents, as well as coinfected sandflies (Bichaud et al 2011, Es-Sette et al 2014, Faucher et al 2014. Crucial issues on the TOSV natural cycle and disease epidemiology have not yet been completely elucidated, and virus exposure in vertebrate species other than humans has only been superficially explored (Navarro-Mari et al 2011). Recently, canine and feline TOSV infections as well as Leishmania and TOSV coinfected dogs in the Mediterranean region of Turkey have been reported (Dincer et al 2015).…”
mentioning
confidence: 99%
“…some of these viruses (Navarro-Marí et al 2011, Alkan et al 2013, Sakhria et al 2014, Dincer et al 2015, Tahir et al 2016); accordingly they can serve as sentinels for the presence of the corresponding viruses. There is no undisputable evidence that birds can be infected by sandfly-borne phleboviruses, but few studies have addressed this point.…”
Section: Using Veterinary Datamentioning
confidence: 99%